Factors Influencing Student Satisfaction with LMS Mobile Application: A TAM-Based SEM Analysis - Ajlouni, Aseel; AlOmary, Asmaa; Al-Smadi, Mohammad; Al-Abdallat, Mohammad; Abu Awwad, Ferial (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Mobile applications for learning management systems (LMS) are becoming extremely common in higher education institutions, with student satisfaction (SS) being crucial for their adoption and effectiveness. This study addresses the gap in understanding factors influencing SS with LMS mobile applications by employing structural equation modeling (SEM) based on the technology acceptance model (TAM). Quantitative study was adopted in this study, involving 475 undergraduate students. The findings of the study revealed that students’ satisfaction with mobile applications for LMS is significantly and positively influenced by external factors (mobile application self-efficacy, content quality, and enjoyment), as well as perceived ease of use and perceived usefulness. The results provide practical insights for decision-makers, professionals, and developers in higher educational institutes on how to effectively implement e-learning systems using mobile applications.